Pemuliaan Perempuan dan Belis dalam Perkawinan Adat Manggarai - Hairuddin K.; Abdul Malik Iskandar; Harifuddin Harifuddin (Society, 2024)
This study explores the functions and meanings of belis, a traditional dowry or bride price in Manggarai culture, within marriage ceremonies in Mbuit Village, West Manggarai. Employing a descriptive qualitative approach grounded in symbolic interactionism, data were collected through in-depth interviews with cultural informants, supported by observation and literature review, and analyzed using the Miles and Huberman three-step framework. The findings reveal that belis serves as a key cultural element, fostering social integration, promoting harmony, and preserving traditions in Manggarai marriages. Symbolically, belis represents the union of two families (social integration) and signifies an economic exchange. The study also highlights the challenges faced by families, particularly those from lower socio-economic backgrounds, in fulfilling the belis requirements, underscoring its deep cultural significance and the commitment it represents.